2023
DOI: 10.1002/adma.202301784
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Organic Frameworks of High Piezovoltage for Sono‐Piezo Dynamic Therapy

Abstract: Piezoelectric materials produce charges to directly act on cancer medium or promote reactive oxygen species (ROS) generation for novel tumor therapy triggered by sonography. Currently, piezoelectric sonosensitizers are mainly used to catalyze ROS generation by band‐tilting effect for sonodynamic therapy. However, it remains a challenge for piezoelectric sonosensitizers to produce high piezo‐voltages to overcome the band‐gap barrier for direct charge generation. Herein, the Mn‐Ti bimetallic organic framework te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Therefore, a possible mechanism was proposed (Figure i), under US or 1064 nm light irradiation, electrons of Au NPs transferred to the SM NPs. Simultaneously, the photogenerated or sound-generated carriers generated inside the SM NPs are separated by the built-in electric field, transmitted through the π–π channel, and reached on the surface of the SM NPs in the end. ,, The generated electrons can convert O 2 into intermediate superoxide anion radicals ( • O 2 – ), and then the generated holes can further oxidize • O 2 – to 1 O 2 . The SMA heterostructures significantly enhances the separation of electrons and holes and improves catalytic efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a possible mechanism was proposed (Figure i), under US or 1064 nm light irradiation, electrons of Au NPs transferred to the SM NPs. Simultaneously, the photogenerated or sound-generated carriers generated inside the SM NPs are separated by the built-in electric field, transmitted through the π–π channel, and reached on the surface of the SM NPs in the end. ,, The generated electrons can convert O 2 into intermediate superoxide anion radicals ( • O 2 – ), and then the generated holes can further oxidize • O 2 – to 1 O 2 . The SMA heterostructures significantly enhances the separation of electrons and holes and improves catalytic efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Wang et al prepared Mn–Ti bimetallic organic framework tetragonal nanosheets (MT-MOF-TNSs). 63 A novel sono-piezo dynamic therapy (SPDT) of the MT-MOF-TNS was proposed for the treatment of tumours (Fig. 5).…”
Section: Applications Of Piezoelectric Mofs In the Treatment Of Tumoursmentioning
confidence: 99%
“…Recently, different research groups have reported pioneering examples of MOFs themselves as efficient nanocatalysts and theranostic agents. 122–132 According to the function roles of MOFs in the construction of CDT agents, two categories of MOF-based nanocatalysts will be summarized in this part. The first section will elaborate on MOFs as nanocarriers of CDT agents by in situ hybridization or post-synthetic modification.…”
Section: Strategies To Construct Hybrid Cdt Agents Based On Diverse N...mentioning
confidence: 99%
“…For example, Wang and coworkers recently reported a Mn-Ti bimetallic MOF (MT-MOF) with non-centrosymmetric SBUs for novel sono-piezo-chemo-dynamic therapy, which is constructed by incorporating Mn elements in the SBUs of a tetragonal Ti-MOF. 128 The formed non-centrosymmetric SBUs of hybrid Mn-Ti-oxo cyclic octamer were effective electric dipoles with heterogeneous charge distribution, which enables MT-MOF to generate a strong sono-piezoelectricity under a low-intensity ultrasound. Specifically, such piezoelectric MT-MOF can convert sonomechanics into electricity to produce a high piezovoltage to excite charges, which depolarize the mitochondrial and plasma membrane potentials and lead to abundant ROS production for novel sono-piezo-dynamic therapy with remarkable antitumor efficacy.…”
Section: Strategies To Construct Hybrid Cdt Agents Based On Diverse N...mentioning
confidence: 99%